2023
DOI: 10.3390/ijms241311013
|View full text |Cite
|
Sign up to set email alerts
|

Stealth Liposomes Encapsulating a Potent ACAT1/SOAT1 Inhibitor F12511: Pharmacokinetic, Biodistribution, and Toxicity Studies in Wild-Type Mice and Efficacy Studies in Triple Transgenic Alzheimer’s Disease Mice

Abstract: Cholesterol is essential for cellular function and is stored as cholesteryl esters (CEs). CEs biosynthesis is catalyzed by the enzymes acyl-CoA:cholesterol acyltransferase 1 and 2 (ACAT1 and ACAT2), with ACAT1 being the primary isoenzyme in most cells in humans. In Alzheimer’s Disease, CEs accumulate in vulnerable brain regions. Therefore, ACATs may be promising targets for treating AD. F12511 is a high-affinity ACAT1 inhibitor that has passed phase 1 safety tests for antiatherosclerosis. Previously, we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…In response to the challenge of the BBB, researchers have found that liposomes modified with various ligands exhibit significant advantages in penetrating the BBB and targeting lesions associated with different diseases. Consequently, there is an anticipation that encapsulating drugs in liposomes will increase drug concentration and ultimately achieve efficient treatment of diseases (S. De La Torre et al, 2023;J. Wang, Kong, et al, 2022).…”
Section: Application Of Liposomes In Brain Repairmentioning
confidence: 99%
“…In response to the challenge of the BBB, researchers have found that liposomes modified with various ligands exhibit significant advantages in penetrating the BBB and targeting lesions associated with different diseases. Consequently, there is an anticipation that encapsulating drugs in liposomes will increase drug concentration and ultimately achieve efficient treatment of diseases (S. De La Torre et al, 2023;J. Wang, Kong, et al, 2022).…”
Section: Application Of Liposomes In Brain Repairmentioning
confidence: 99%